Pengaruh Sosial Media dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Platform Tokopedia di Tangerang Selatan - Sultan Afryan Novendra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research reviews the influence of social media and trust on purchasing decisions on the Tokopedia platform in South Tangerang. The background reflects significant changes in consumer behavior due to developments in information technology, especially in online commerce. The goal is to analyze the factors that influence purchasing decisions with a focus on social media and consumer trust. Quantitative methods are used to collect and analyze data from consumers in the region. Research findings show that although social media does not have a positive influence on purchasing decisions, consumer trust has a significant influence on purchasing decisions. The implication is the importance of strengthening consumer trust in building effective marketing strategies on e-commerce platforms, as well as the need to develop theories of consumer behavior in the digital era.